Managing in construction supply chains and markets reactive and proactive options for improving performance and relationship management - Cox, Andrew W. (Thomas Telford, 2006)
This text outlines the practical and theoretical basis for thinking analytically about the balance of power in construction supply chains. It presents the practical findings from EPSRC sponsored research, undertaken in conjunction with the construction industry.